Determination of support stiffness of a built-in beam by finite element analysis - Weng, Minglong (Nanyang Technological University, 2022)
Support stiffness of a beam is a measure of the ability of the support to resist deformation (translational and rotational) are caused by the loads applied to the beam. The support stiffness is one of the critical factors in structural analysis. In this report, an attempt is made to characterise the support stiffness of a cantilever beam in terms of equivalent support stiffness values. Finite element analysis is used to determine the stiffness felt at the support of the beam for linear and angular displacement. ANSYS Mechanical APDL software is utilised for finite element analysis. Load-displacement characteristics are evaluated for various lengths of beams. The equivalent support stiffness (translational and rotational) is extracted from the displacement results. The results suggest translational-rotational coupling effects need to be included in the analysis. The coupling effects are modelled by introducing a support stiffness matrix. The support stiffness is found to be valid and useful in predicting the maximum displacement of a beam with any length. As part of the project, the computed stiffness values are applied in the analytical modelling of a cantilever beam including the flexibility effects of the support. Towards this purpose, the classical unit load method (in the textbook) is modified suitably to include the coupling effects of translational and rotary stiffness.